IMPROVING STUDENTS’ READING COMPREHENSION THROUGH SVO (SUBJECT VERB OBJECT) MAPPING STRATEGY ( A CLASSROOM ACTION RESEARCH) AT TENTH GRADE STUDENTS IN SMKN - Ainun Huda (Language-Edu, 2020)
The goal of this study is to improve reading comprehensin of the students in SMKN 1 Kemlagi. The development of the method is taken in this study because it is very important to find the most effective and easy way for student to comprehend reading. The methodological approach of the study is A Class Action Research. The Data collection is gathered by using test and observation, and also by holding pre and post test, to know the students ability before and after the study is conducted. There will be one class to observe in this study, consisting 34 students. The process of the study is started by conducting the preliminary research to know the former condition of the learning process in teaching reading. The study will see the existing of the syllabus, by analizing the basic competency, mean of the learning process, indicators, material and the teaching strategy. Moreover, it will be the background to develop further study in developing the teaching strategy in reading. SVO mapping Strategy is used in reading mastery process. It is done to guide the students to achieve reading skill. Finally, the result of this study shows that this method can be used as the alternative strategy in teaching and learning process in the class. Students can be easier to comprehend the content of the passage .Keywords : reading, reading strategy, classroom action research